Nonlinear beam interaction with electromagnetic waves in infinite plasma - Volokitin, A.S.; Krafft, C. (Вопросы атомной науки и техники, 2000)
In the presence of strong dissipation, the nonlinear interaction of a monoenergetic cylindrical or spiraling electron beam with a packet of whistlers or lower hybrid waves differs considerably from the nondissipative case. The evolution of the beam-waves system exhibits a strong tendency to self-organization and leads to the formation of electron bunches continuously decelerated by waves. Strong dissipation prevents the phase mixing required for the quasilinear theory, keeps waves' phases in the packet correlated and allows the formation of dynamically stable bunches. The nonlinear model developed here considers whistler and lower hybrid waves emission through Cherenkov and cyclotron resonances by a density modulated thin electron beam.